Producto escalar - Gutiérrez-Montenegro, Marco (My University, 2017)
Introduce la geometría de los vectores usando el concepto de vector mediante la interpretación analítica o algebraica.

It introduces the geometry of vectors using the concept of vector through analytic or algebraic interpretation.
Keywords: Vectores; Multiplicaciones matrices; Geometría vectorial